2018
DOI: 10.1017/s0030605317001545
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about the life-history traits of widely hunted tropical mammals?

Abstract: We synthesize information on parameters useful for managing the hunting of two common mammal species that are important for local people in the Neotropics and Africa: Cuniculus paca and Philantomba monticola, respectively. We highlight the scarcity of data available on the parameters needed to manage these two species sustainably. As most of the studies were conducted > 40 years ago, we stress the need to supplement the information available using methodological and technical innovations. In particular, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…dorsalis and blue duiker C . monticola (also known under the scientific name Philantomba monticola ) [ 36 , 37 ] were selected as our case study based on availability of independent and published empirical estimates of population parameters and their relative importance for wild meat supply in sub-Saharan Africa [ 38 ]. Candidate studies were identified using Google Scholar and Web of Science (using search terms: bushmeat, wild meat, tropical, Africa), and by searching the cited references in the collated papers.…”
Section: Methodsmentioning
confidence: 99%
“…dorsalis and blue duiker C . monticola (also known under the scientific name Philantomba monticola ) [ 36 , 37 ] were selected as our case study based on availability of independent and published empirical estimates of population parameters and their relative importance for wild meat supply in sub-Saharan Africa [ 38 ]. Candidate studies were identified using Google Scholar and Web of Science (using search terms: bushmeat, wild meat, tropical, Africa), and by searching the cited references in the collated papers.…”
Section: Methodsmentioning
confidence: 99%
“…Hunting by women and children is rarely recorded, as it is often opportunistic hunting, generally of small birds and mammals, crayfish and reptiles, within the course of other livelihood activities such as agriculture. Including their hunting offtake, however, can make a difference to calculations of overall use of wild meat and the social and ecological impacts (Goodman et al 1985;Hewlett 2005;Bonwitt et al 2017;Ingram et al 2018;van Vliet et al 2018).…”
Section: Hunter Characteristicsmentioning
confidence: 99%
“…This is particularly likely to happen in newly urbanized areas, where urban populations still retain the skills necessary for rural harvesting. Human populations that are displaced by conflict often become reliant on wild meat due to the loss of their normal sources of food and income, and an absence of alternatives (de Merode and Cowlishaw, 2006;Loucks et al 2009;Nackoney et al 2014;Takamura, 2015;van Vliet et al 2017bvan Vliet et al , 2018. For instance, a sizable illegal wild meat trade has emerged in Tanzania owing to the influx of refugees from neighboring Burundi, DRC and Rwanda; other sources of protein are scarce in the refugee camps (Jambiya et al 2007).…”
Section: National Economic Crisis Poverty and Conflictmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to its wide distribution, occurrence in a number of protected areas, and presumed large population, the paca is unlikely to be declining and, consequently, it is categorized as being of least concern on the IUCN Red List [ 17 ]. Indeed, van Vliet and Nasi [ 18 ] suggest that the paca’s behavioural plasticity traits are important contributors to its resilience to hunting.…”
Section: Introductionmentioning
confidence: 99%